Analysis of hygienic-sanitary indicators in chilled raw bovine milk marketed in the microregion of Ji-Paraná - Rondônia - Brazil (Research, Society and Development, 2021)
The aimed of the study was to analyze the hygienic-sanitary parameters of chilled raw bovine milk under the Federal Inspection System (SIF), commercialized d in the microregion of Ji-Paraná - RO, Brazil. The study was carried out with 600 samples collected over 90 days from rural properties producing bovine milk. The somatic cell count (CCS) and total bacterial count (CTB) were performed in the laboratory. The data were analyzed and classified by the quality standard referring to the normative instructions nº 76 and 77 of the Ministry of Agriculture, Livestock and Supply (MAPA), the study of proportion of single sample (α=0.05) was carried out by the Action Stat® software 3.7. Based on the results, it was evidenced that 52% (312/600) of the samples presented CBT in compliance with the legislation, as well as, for the CCS test, 85.2% (511/600). And, when analyzing the hygienic-sanitary indicators of milk, the CTB average ranged from 600,000 CFU/mL to 860,000 CFU/mL, while the CCS fluctuated from 320,000 CCS/mL to 350,000 CCS/mL. The analyzed samples showed a quarterly average higher than that recommended by IN nº 76, thus not being approved for CTB. However, regarding the CCS assessment, it is observed that the sample group is in accordance with what is recommended. There is a need to improve good hygiene practices throughout the process of obtaining and maintaining chilled raw milk, with a view to improving the quality of bovine milk sold in the region, and consequently meeting the requirements established by federal legislation.